Chain surface treatment process

Through a process combining spray coating, liquid nitrogen spray-ultrasonic coupling and coating treatment, the problem of insufficient chemical corrosion resistance of the chain is solved, and the acid, alkali, salt resistance and mechanical properties of the chain are significantly improved.

CN119588599APending Publication Date: 2025-03-11ANHUI JIXI HUISHAN CHAIN TRANSMISSION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411511637.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The chain is susceptible to corrosion during use, resulting in reduced strength and short service life. It is difficult for the prior art to effectively improve its chemical corrosion resistance.

Method used

A chain surface treatment process is adopted, including spray coating, liquid nitrogen spray-ultrasonic coupling treatment and coating treatment. The treatment agent contains components such as fulvic acid, tartaric acid, Tween 60, rosin, shellac and propylene glycol. Internal stress is generated by liquid nitrogen spraying and ultrasonic treatment, and the surface protection of the chain is further enhanced by special coatings.

Benefits of technology

It significantly improves the chain's acid, alkali and salt resistance, extends the chain's service life, and improves its mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588599A_ABST
    Figure CN119588599A_ABST
Patent Text Reader

Abstract

The invention discloses a chain surface treatment process, which belongs to the technical field of mechanical surface treatment, and comprises the following steps: (1) spray coating treatment; (2) liquid nitrogen spraying-ultrasonic coupling treatment; and (3) coating treatment. According to the chain surface treatment process, spraying treatment, liquid nitrogen spraying, ultrasonic coupling treatment and coating treatment are matched to treat the chain, the acid resistance, the alkali resistance and the salt resistance of the chain are remarkably improved, and the quality of the chain is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mechanical surface treatment, in particular to a chain surface treatment process. Background Art

[0002] A chain is an assembly consisting of multiple metal rings or links connected to each other, usually used to transmit mechanical force or as a supporting structure. Chain is an important mechanical component and is widely used in various machines and equipment.

[0003] Since the chain will be affected by the environment during use, such as corrosion, which will cause the strength to decrease and the service life to be shortened, it is urgent to research and develop a treatment method to improve the chemical corrosion resistance of the chain. Summary of the invention

[0004] The purpose of the present invention is to provide a chain surface treatment process to solve the deficiencies in the prior art.

[0005] The technical solution adopted by the present invention is as follows: A chain surface treatment process comprises the following steps: (1) Spraying treatment: Spray the treatment agent evenly onto the surface of the chain, and dry it for later use after completion; (2) Liquid nitrogen spray-ultrasonic coupling treatment: Evenly spraying liquid nitrogen onto the surface of the chain after the spraying treatment in step (1), and immediately placing it in an ultrasonic environment for ultrasonic treatment; (3) Coating treatment: The specially prepared coating is evenly applied to the surface of the chain treated in step (2), and then dried.

[0006] Furthermore, the components and corresponding weight percentages of the treatment agent in step (1) are as follows: 1-2% fulvic acid, 2-3% tartaric acid, 10-14% Tween 60, 7-11% rosin, 3-7% shellac, 0.7-0.9% propylene glycol, and the balance is deionized water. 1-2% fulvic acid, 2-3% tartaric acid, 10-14% Tween 60, 7-11% rosin, 3-7% shellac, 0.7-0.9% propylene glycol, and the balance is deionized water.

[0007] By adopting the above technical solution, the treatment agent is evenly sprayed onto the surface of the chain. The treatment agent quickly migrates on the surface of the chain, causing slight corrosion on the surface of the chain. At the same time, it can also form a thin film protective layer on its surface, laying an easy foundation for subsequent operations.

[0008] Furthermore, during the ultrasonic treatment in step (2), the frequency of the ultrasonic wave is controlled to be 20-30 kHz, and the ultrasonic treatment time is 23-27 min.

[0009] By adopting the above technical solution, liquid nitrogen is sprayed onto the surface of the chain, and the temperature drops rapidly, resulting in a great temperature difference between the inside and outside of the chain. However, due to the restraining effect of the film, the temperature difference between the inside and outside generates instantaneous internal stress inside the chain. At the same time, ultrasonic treatment is performed. Under the effects of ultrasonic sound flow effect, cavitation effect, thermal effect and other effects, the internal stress breaks through the restraining effect of the film, and the treatment agent further produces weak etching on the surface of the chain. At the same time, due to the effect of internal stress, the chain can be effectively prevented from stress deformation, thereby improving the mechanical properties of the chain.

[0010] Furthermore, the preparation of the special coating described in step (3) comprises the following steps: 1) Cold plasma treatment: The natural resin and the epoxy resin are mixed in a weight ratio of 1:7-9 and placed in an air DBD cold plasma treatment device, and the device is started for cold plasma treatment. After completion, the mixture A is taken out for use; 2) Flame treatment: The filler and the mixture A obtained in step 1) are mixed at a weight ratio of 1:35-39 and then placed on the outer flame for flame treatment, and after the mixture is completed, a mixture B is obtained for use; 3) Heating ionization treatment: The mixture B obtained in step 2) is immersed in the treatment liquid, and then the treatment liquid immersed in the mixture B is poured into the electrolytic cell, and the power is turned on to perform heating and ionization treatment. After completion, the mixture is filtered and dried to obtain the mixture C for use; 4) Decentralized processing: Weigh corresponding weight portions of the mixture C obtained in step 3), 92-98 parts, 1-1.4 parts of polydimethylsiloxane, 2.1-2.5 parts of zinc stearate, 4.2-4.8 parts of chitosan, 3.5-4.5 parts of castor oil, 0.65-0.85 parts of polyether polyester modified organosiloxane, 3.2-3.8 parts of silicone oil, and 35-45 parts of water, and place them together in a dispersion tank, and disperse them uniformly at a speed of 700-900 rpm to obtain a dispersion for later use; 5) Photochemical treatment: The dispersion obtained in step 4) is placed in an ultraviolet environment for ultraviolet light irradiation treatment, and then placed in a stirring tank for ultrasonic degassing treatment.

[0011] Furthermore, the power of the cold plasma treatment in step 1) is 3-4 kW, and the number of treatments is 7-9 times.

[0012] Furthermore, the filler in step 2) is at least one of diatomaceous earth, graphene, attapulgite, and nano zinc oxide.

[0013] Furthermore, during the flame treatment in step 2), the horizontal distance between the mixture A and the outer flame of the flame is controlled to be 0.5-0.9 cm, and the treatment time is 13-17 min.

[0014] Furthermore, the components and corresponding weight percentages in the treatment solution described in step 3) are: ammonium chloride 2.2-2.8%, ammonia water 5.5-6.5%, diammonium phosphate 1.2-1.8%, triethyl chloride or tributyltin 0.95-1.25%, and the balance is pure water.

[0015] Furthermore, during the heating ionization treatment in step 3), the temperature in the treatment liquid is controlled to be 72-78° C., the voltage is 190-210 V, the current is 7-9 A, and the treatment time is 20-24 min.

[0016] Furthermore, during the ultraviolet light irradiation treatment in step 5), the wavelength of the ultraviolet light is controlled to be 250-350 nm, and the treatment time is 70-110 min.

[0017] By adopting the above technical solution, the specially prepared coating is evenly coated on the surface of the chain, acts on the chain quickly, and adheres tightly to the surface of the chain, thereby enhancing the chemical corrosion resistance of the chain.

[0018] The present invention has the following beneficial effects: The present application provides a chain surface treatment process, which combines spraying treatment, liquid nitrogen spraying, ultrasonic coupling treatment, and coating treatment to treat the chain, significantly improving the acid resistance, alkali resistance, and salt resistance of the chain, and effectively improving the quality of the chain. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a comparison chart of acid resistance, alkali resistance and salt resistance test data of various embodiments in the specific implementation method of this application. DETAILED DESCRIPTION

[0020] The following will be described clearly and completely in conjunction with the technical solutions of the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0021] A chain surface treatment process comprises the following steps: (1) Spraying treatment: Spray the treatment agent evenly onto the surface of the chain, and dry it for later use after completion; (2) Liquid nitrogen spray-ultrasonic coupling treatment: Evenly spraying liquid nitrogen onto the surface of the chain after the spraying treatment in step (1), and immediately placing it in an ultrasonic environment for ultrasonic treatment; (3) Coating treatment: The specially prepared coating is evenly applied to the surface of the chain treated in step (2), and then dried.

[0022] The components and corresponding weight percentages of the treatment agent described in step (1) are: fulvic acid 1%, tartaric acid 2%, Tween 60 10%, rosin 7%, shellac 3%, propylene glycol 0.7%, and the balance is deionized water.

[0023] During the ultrasonic treatment in step (2), the frequency of the ultrasonic wave is controlled to be 20 kHz, and the ultrasonic treatment time is 23 minutes.

[0024] The preparation of the special coating described in step (3) comprises the following steps: 1) Cold plasma treatment: The natural resin and the epoxy resin were mixed in a weight ratio of 1:7 and placed in an air DBD cold plasma treatment device, and the device was started for cold plasma treatment. After completion, the mixture A was taken out for use; 2) Flame treatment: The filler and the mixture A obtained in step 1) are mixed at a weight ratio of 1:35 and then placed on the outer flame for flame treatment, and after the mixture is completed, a mixture B is obtained for use; 3) Heating ionization treatment: The mixture B obtained in step 2) is immersed in the treatment liquid, and then the treatment liquid immersed in the mixture B is poured into the electrolytic cell, and the power is turned on to perform heating and ionization treatment. After completion, the mixture is filtered and dried to obtain the mixture C for use; 4) Decentralized processing: Weigh corresponding weight portions of the mixture C obtained in step 3), 92 parts, 1 part of polydimethylsiloxane, 2.1 parts of zinc stearate, 4.2 parts of chitosan, 3.5 parts of castor oil, 0.65 parts of polyether polyester modified organosiloxane, 3.2 parts of silicone oil, and 35 parts of water, and place them together in a dispersion tank, and disperse them uniformly at a speed of 700 rpm to obtain a dispersion for later use; 5) Photochemical treatment: The dispersion obtained in step 4) is placed in an ultraviolet environment for ultraviolet light irradiation treatment, and then placed in a stirring tank for ultrasonic degassing treatment.

[0025] The power of the cold plasma treatment in step 1) is 3 kW, and the number of treatments is 7 times.

[0026] The filler in step 2) is at least one of diatomaceous earth, graphene, attapulgite, and nano zinc oxide.

[0027] During the flame treatment in step 2), the horizontal distance between the mixture A and the outer flame of the flame was controlled to be 0.5 cm, and the treatment time was 13 minutes.

[0028] The components and corresponding weight percentages of the treatment solution in step 3) are: 2.2% ammonium chloride, 5.5% ammonia water, 1.2% diammonium phosphate, 0.95% triethyl chloride or tributyltin, and the balance is pure water.

[0029] During the heating ionization treatment in step 3), the temperature in the treatment liquid was controlled to be 72° C., the voltage was 190 V, the current was 7 A, and the treatment time was 20 min.

[0030] During the ultraviolet light irradiation treatment described in step 5), the wavelength of the ultraviolet light is controlled to be 250 nm, and the treatment time is 70 minutes. Example 2

[0031] A chain surface treatment process comprises the following steps: (1) Spraying treatment: Spray the treatment agent evenly onto the surface of the chain, and dry it for later use after completion; (2) Liquid nitrogen spray-ultrasonic coupling treatment: Evenly spraying liquid nitrogen onto the surface of the chain after the spraying treatment in step (1), and immediately placing it in an ultrasonic environment for ultrasonic treatment; (3) Coating treatment: The specially prepared coating is evenly applied to the surface of the chain treated in step (2), and then dried.

[0032] The components and corresponding weight percentages of the treatment agent described in step (1) are: fulvic acid 1.5%, tartaric acid 2.5%, Tween 60 12%, rosin 9%, shellac 5%, propylene glycol 0.8%, and the balance is deionized water.

[0033] During the ultrasonic treatment in step (2), the frequency of the ultrasonic wave is controlled to be 25 kHz, and the ultrasonic treatment time is 25 min.

[0034] The preparation of the special coating described in step (3) comprises the following steps: 1) Cold plasma treatment: The natural resin and the epoxy resin were mixed in a weight ratio of 1:8 and placed in an air DBD cold plasma treatment device, and the device was started for cold plasma treatment. After the treatment was completed, the mixture A was taken out for use; 2) Flame treatment: The filler and the mixture A obtained in step 1) are mixed at a weight ratio of 1:37 and then placed on the outer flame for flame treatment, and after the mixture is completed, a mixture B is obtained for use; 3) Heating ionization treatment: The mixture B obtained in step 2) is immersed in the treatment liquid, and then the treatment liquid immersed in the mixture B is poured into the electrolytic cell, and the power is turned on to perform heating and ionization treatment. After completion, the mixture is filtered and dried to obtain the mixture C for use; 4) Decentralized processing: Weigh corresponding weight portions of 95 parts of the mixture C obtained in step 3), 1.2 parts of polydimethylsiloxane, 2.3 parts of zinc stearate, 4.5 parts of chitosan, 4 parts of castor oil, 0.75 parts of polyether polyester modified organosiloxane, 3.5 parts of silicone oil, and 40 parts of water, place them together in a dispersion tank, and disperse them uniformly at a speed of 800 rpm to obtain a dispersion for later use; 5) Photochemical treatment: The dispersion obtained in step 4) is placed in an ultraviolet environment for ultraviolet light irradiation treatment, and then placed in a stirring tank for ultrasonic degassing treatment.

[0035] The power of the cold plasma treatment in step 1) is 3.5 kW, and the number of treatments is 8 times.

[0036] The filler in step 2) is at least one of diatomaceous earth, graphene, attapulgite, and nano zinc oxide.

[0037] During the flame treatment in step 2), the horizontal distance between the mixture A and the outer flame of the flame is controlled to be 0.7 cm, and the treatment time is 15 minutes.

[0038] The components and corresponding weight percentages in the treatment solution described in step 3) are: 2.5% ammonium chloride, 6% ammonia water, 1.5% diammonium phosphate, 1.1% triethyl chloride or tributyltin, and the balance is pure water.

[0039] During the heating ionization treatment in step 3), the temperature in the treatment liquid was controlled to be 75° C., the voltage was 200 V, the current was 8 A, and the treatment time was 22 min.

[0040] During the ultraviolet light irradiation treatment described in step 5), the wavelength of the ultraviolet light is controlled to be 300 nm, and the treatment time is 90 minutes. Example 3

[0041] A chain surface treatment process comprises the following steps: (1) Spraying treatment: Spray the treatment agent evenly onto the surface of the chain, and dry it for later use after completion; (2) Liquid nitrogen spray-ultrasonic coupling treatment: Evenly spraying liquid nitrogen onto the surface of the chain after the spraying treatment in step (1), and immediately placing it in an ultrasonic environment for ultrasonic treatment; (3) Coating treatment: The specially prepared coating is evenly applied to the surface of the chain treated in step (2), and then dried.

[0042] The components and corresponding weight percentages of the treatment agent described in step (1) are: fulvic acid 2%, tartaric acid 3%, Tween 60 14%, rosin 11%, shellac 7%, propylene glycol 0.9%, and the balance is deionized water.

[0043] During the ultrasonic treatment in step (2), the frequency of the ultrasonic wave is controlled to be 30 kHz, and the ultrasonic treatment time is 27 minutes.

[0044] The preparation of the special coating described in step (3) comprises the following steps: 1) Cold plasma treatment: The natural resin and the epoxy resin were mixed in a weight ratio of 1:9 and placed in an air DBD cold plasma treatment device, and the device was started for cold plasma treatment. After completion, the mixture A was taken out for use; 2) Flame treatment: The filler and the mixture A obtained in step 1) are mixed at a weight ratio of 1:39 and then placed on the outer flame for flame treatment, and after the mixture is completed, a mixture B is obtained for use; 3) Heating ionization treatment: The mixture B obtained in step 2) is immersed in the treatment liquid, and then the treatment liquid immersed in the mixture B is poured into the electrolytic cell, and the power is turned on to perform heating and ionization treatment. After completion, the mixture is filtered and dried to obtain the mixture C for use; 4) Decentralized processing: Weigh corresponding weight portions of the mixture C obtained in step 3), 98 parts, 1.4 parts of polydimethylsiloxane, 2.5 parts of zinc stearate, 4.8 parts of chitosan, 4.5 parts of castor oil, 0.85 parts of polyether polyester modified organosiloxane, 3.8 parts of silicone oil, and 45 parts of water, and place them together in a dispersion tank, and disperse them uniformly at a speed of 900 rpm to obtain a dispersion for later use; 5) Photochemical treatment: The dispersion obtained in step 4) is placed in an ultraviolet environment for ultraviolet light irradiation treatment, and then placed in a stirring tank for ultrasonic degassing treatment.

[0045] The power of the cold plasma treatment in step 1) is 4 kW, and the number of treatments is 9 times.

[0046] The filler in step 2) is at least one of diatomaceous earth, graphene, attapulgite, and nano zinc oxide.

[0047] During the flame treatment in step 2), the horizontal distance between the mixture A and the outer flame of the flame was controlled to be 0.9 cm, and the treatment time was 17 minutes.

[0048] The components and corresponding weight percentages in the treatment solution described in step 3) are: 2.8% ammonium chloride, 6.5% ammonia water, 1.8% diammonium phosphate, 1.25% triethyl chloride or tributyltin, and the balance is pure water.

[0049] During the heating ionization treatment in step 3), the temperature in the treatment liquid was controlled to be 78° C., the voltage was 210 V, the current was 9 A, and the treatment time was 24 min.

[0050] During the ultraviolet light irradiation treatment described in step 5), the wavelength of the ultraviolet light is controlled to be 350 nm, and the treatment time is 110 minutes.

[0051] Comparative Example 1 Compared with Example 2, the entire process of step (1) spraying treatment is omitted in Comparative Example 1, and other method steps are the same.

[0052] Comparative Example 2 Compared with Example 2, in this Comparative Example 2, in step (2) liquid nitrogen spray-ultrasonic coupling treatment, the liquid nitrogen spray treatment is omitted, and other method steps are the same.

[0053] Comparative Example 3 Compared with Example 2, in this comparative example 3, in step (2) liquid nitrogen spray-ultrasonic coupling treatment, ultrasonic treatment is omitted, and other method steps are the same.

[0054] Comparative Example 4 Compared with Example 2, this comparative example 4 omits the entire process of step (2) liquid nitrogen spray-ultrasonic coupling treatment, and other method steps are the same.

[0055] Comparative Example 5 Compared with Example 2, the entire process of step (3) spraying treatment is omitted in Comparative Example 5, and other method steps are the same.

[0056] In order to compare the technical effects of the present application, chains of the same batch and specification were selected as test objects, and the selected chains were randomly divided into 7 groups of equal quality and quantity, of which 6 groups were test groups and 1 group was a blank control group. Then, the methods of the above-mentioned embodiment 2 and comparative embodiments 1 to 5 were used to treat the chains in each group. After completion, 6 chains were taken from each group (including the blank control group) and immersed in 10moL / L HCl solution, 6 chains were taken and immersed in 10moL / L NaOH solution, and 6 chains were taken and immersed in 10moL / L NaCl solution. The corrosion time (h) of each group of chains was observed and recorded. Specific test comparison data are as follows: Figure 1 shown.

[0057] Depend on Figure 1 It can be seen that the present application provides a chain surface treatment process, which combines spraying treatment, liquid nitrogen spraying, ultrasonic coupling treatment, and coating treatment to treat the chain, which significantly improves the chain's acid resistance, alkali resistance, and salt resistance, and effectively improves the quality of the chain.

[0058] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.

Claims

1. A chain surface treatment process, characterized in that: The steps include: (1) Spraying treatment: Spray the treatment agent evenly onto the surface of the chain, and dry it for later use after completion; (2) Liquid nitrogen spray-ultrasonic coupling treatment: Evenly spraying liquid nitrogen onto the surface of the chain after the spraying treatment in step (1), and immediately placing it in an ultrasonic environment for ultrasonic treatment; (3) Coating treatment: The specially prepared coating is evenly applied to the surface of the chain treated in step (2), and then dried.

2. A chain surface treatment process according to claim 1, characterized in that: The components and corresponding weight percentages of the treatment agent described in step (1) are: fulvic acid 1-2%, tartaric acid 2-3%, Tween 60 10-14%, rosin 7-11%, shellac 3-7%, propylene glycol 0.7-0.9%, and the balance is deionized water.

3. A chain surface treatment process according to claim 1, characterized in that: During the ultrasonic treatment in step (2), the frequency of the ultrasonic wave is controlled to be 20-30 kHz, and the ultrasonic treatment time is 23-27 minutes.

4. A chain surface treatment process according to claim 1, characterized in that: The preparation of the special coating described in step (3) comprises the following steps: 1) Cold plasma treatment: The natural resin and the epoxy resin are mixed in a weight ratio of 1:7-9 and placed in an air DBD cold plasma treatment device, and the device is started for cold plasma treatment. After completion, the mixture A is taken out for use; 2) Flame treatment: The filler and the mixture A obtained in step 1) are mixed at a weight ratio of 1:35-39 and then placed on the outer flame for flame treatment, and after the mixture is completed, a mixture B is obtained for use; 3) Heating ionization treatment: The mixture B obtained in step 2) is immersed in the treatment liquid, and then the treatment liquid immersed in the mixture B is poured into the electrolytic cell, and the power is turned on to perform heating and ionization treatment. After completion, the mixture is filtered and dried to obtain the mixture C for use; 4) Decentralized processing: Weigh corresponding weight portions of the mixture C obtained in step 3), 92-98 parts, 1-1.4 parts of polydimethylsiloxane, 2.1-2.5 parts of zinc stearate, 4.2-4.8 parts of chitosan, 3.5-4.5 parts of castor oil, 0.65-0.85 parts of polyether polyester modified organosiloxane, 3.2-3.8 parts of silicone oil, and 35-45 parts of water, and place them together in a dispersion tank, and disperse them uniformly at a speed of 700-900 rpm to obtain a dispersion for later use; 5) Photochemical treatment: The dispersion obtained in step 4) is placed in an ultraviolet environment for ultraviolet light irradiation treatment, and then placed in a stirring tank for ultrasonic degassing treatment.

5. A chain surface treatment process according to claim 4, characterized in that: The power of the cold plasma treatment in step 1) is 3-4 kW, and the number of treatments is 7-9 times.

6. A chain surface treatment process according to claim 4, characterized in that: The filler in step 2) is at least one of diatomaceous earth, graphene, attapulgite, and nano zinc oxide.

7. A chain surface treatment process according to claim 4, characterized in that: During the flame treatment in step 2), the horizontal distance between the mixture A and the outer flame of the flame is controlled to be 0.5-0.9 cm, and the treatment time is 13-17 minutes.

8. A chain surface treatment process according to claim 4, characterized in that: The components and corresponding weight percentages in the treatment solution described in step 3) are: ammonium chloride 2.2-2.8%, ammonia water 5.5-6.5%, diammonium phosphate 1.2-1.8%, triethyl chloride or tributyltin 0.95-1.25%, and the balance is pure water.

9. A chain surface treatment process according to claim 4, characterized in that: During the heating ionization treatment described in step 3), the temperature in the treatment liquid is controlled to be 72-78° C., the voltage is 190-210 V, the current is 7-9 A, and the treatment time is 20-24 min.

10. A chain surface treatment process according to claim 4, characterized in that: During the ultraviolet light irradiation treatment described in step 5), the wavelength of the ultraviolet light is controlled to be 250-350 nm, and the treatment time is 70-110 min.